2011
DOI: 10.1016/j.bone.2010.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Increasing duration of type 1 diabetes perturbs the strength–structure relationship and increases brittleness of bone

Abstract: Type 1 diabetes (T1DM) increases the likelihood of a fracture. Despite serious complications in the healing of fractures among those with diabetes, the underlying causes are not delineated for the effect of diabetes on the fracture resistance of bone. Therefore, in a mouse model of T1DM, we have investigated the possibility that a prolonged state of diabetes perturbs the relationship between bone strength and structure (i.e., affects tissue properties). At 10, 15, and 18 weeks following injection of streptozot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
87
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 57 publications
11
87
0
2
Order By: Relevance
“…It is possible that subjecting the animals to a longer period of hyperglycaemia would cause further deterioration in the material properties of bone. This has been confirmed by Nyman et al [23] in a mouse model exposed to DM for up to 18 wk, in which further deterioration in mechanical properties was observed with longer exposure.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It is possible that subjecting the animals to a longer period of hyperglycaemia would cause further deterioration in the material properties of bone. This has been confirmed by Nyman et al [23] in a mouse model exposed to DM for up to 18 wk, in which further deterioration in mechanical properties was observed with longer exposure.…”
Section: Discussionsupporting
confidence: 69%
“…However, the changes that occur are probably not only to be result of changes in mechanical properties but are probably also due to inherent detrimental changes which occur in the structural material properties. This theory has been confirmed in a mouse model where significant differences were observed in the strength-structure relationship, with reductions to the tissue mineral density of bone in DM, which became apparent after only 10 wk [23] . Our experimental model subjected the D group of rats to uncontrolled levels of hyperglycaemia.…”
Section: Discussionmentioning
confidence: 67%
“…Specifically, T1DM patients have an absolute deficiency of insulin-like growth factor 1 (IGF1), that results in impaired bone formation and lower peak bone mass. Conversely, T2DM patients may display increased BMD due to both increased mechanical loading and hyperinsulinaemia; however, both T1DM and T2DM patients have microarchitectural bone changes, resulting in bone which has an inferior quality compared with that of the general population (Brown 2004, Yamagishi et al 2005, Melton et al 2008, Milczarczyk 2008, Nyman et al 2011. As DM is beyond the remit of this review, we direct the reader to the review by Jackuliak & Payer (2014).…”
Section: Insulin and The Insulin Receptormentioning
confidence: 99%
“…Several studies using STZ-injected rodent models have been published in the last decade and reported inconsistent data on the effect of T1DM on bone tissue material properties, i.e., the mineral and organic component of the bone matrix [12][13][14][15]. Previous studies seem suggest that bone microarchitecture deterioration appears early, while modification of intrinsic material, as determined by bone toughness, occurs later [16]. Furthermore, an inherent problem with the STZ model is that this compound is often injected around 10 weeks of age, and the general duration of studies is around 10-12 weeks.…”
Section: Introductionmentioning
confidence: 99%